Corylin suppresses metastasis of breast cancer cells by modulating miR-34c/LINC00963 target. Issue 1 (1st January 2021) - Liu, Shourong; Wang, Li; Zhang, Run
ABSTRACT: Breast cancer is one of the cancers leading to most death cases among women and metastasis is the major cause of breast cancer mortality. In this study, Corylin, the flavonoid compound which is extracted and purified from Psoralea corylifolia L., the effect on breast cancer metastasis was investigated. Corylin showed inhibitory effect on migration and invasion abilities of breast cancer cells. Meanwhile, the epithelial–mesenchymal transition was also regulated by corylin. The long non-coding RNA LINC00963 was found to have a significantly high expression level in breast cancer while it can be down-regulated by corylin. In addition, both wound-healing assay and transwell assay showed that LINC00963 induced breast cancer cells metastasis. MiR-34c was increased by corylin treatment depending on p53, and it was firstly identified that the LINC00963 was a direct target of miR-34c. Corylin was verified here that it prohibited MCF-7 migration and invasion depending on miR-34c/LINC00963 target. In conclusion, corylin suppresses metastasis of breast cancer cells via increasing miR-34c expression, which was dependent on p53. LINC00963 was a direct target of miR-34c and the target axis was necessary for corylin function. Therefore, corylin is a promising drug candidate and LINC00963 can be seen as a promising target in breast cancer treatment